State And Private Schools In Uzbekistan: Their Role In The Education System And Development Prospects - O'ktamova, Mokhigul; Odilova, Mohlaroy (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article analyzes the role of state and private schools operating in the Republic of Uzbekistan in the education system, their theoretical foundations and differences in terms of the quality of education. During the research, the advantages and disadvantages of both types of schools were identified and their adaptation to modern educational requirements was assessed. The results of the article are of practical importance in improving the national education system and increasing the quality of school education. It also highlights how educational reforms implemented by the state and the increasing participation of the private sector affect the quality of school education. The role of state schools in ensuring social equality and innovative approaches of private schools are compared. The results of the study allow us to draw important conclusions for improving educational policy, effectively organizing school activities, and for parents and education specialists.